2020
DOI: 10.1002/ijgo.13396
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clinical performance when intrauterine devices are inserted by different categories of healthcare professional

Abstract: Objective We evaluated clinical performance when the TCu380A intrauterine device (IUD) and the levonorgestrel (LNG) 52‐mg intrauterine system (IUS) were inserted by different categories of healthcare professionals. Methods A retrospective study was conducted at the University of Campinas, Brazil. The medical records were reviewed of all women in whom an IUD was inserted between January 1980 and December 2018, with data for at least 1 year, and for whom information on the healthcare provider who inserted the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
12

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 17 publications
0
10
0
12
Order By: Relevance
“…The training was offered to residents from GO and FM, which similar rates of expulsion and inadequate insertions were shown. A recent Brazilian studied conducted at the University of Campinas shows similar performance results when IUD or LNG-IUS were inserted by medical residents, generalists, or nurses, with no differences in expulsion rates or removal for personal reasons (Laporte et al, 2020). The expulsion rate (8.6%) was higher than the one found in the literature; however, it can be deemed acceptable once we are in training service, and more than 70% of women that desire for IUD have access to the method (Trussell, 2011).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The training was offered to residents from GO and FM, which similar rates of expulsion and inadequate insertions were shown. A recent Brazilian studied conducted at the University of Campinas shows similar performance results when IUD or LNG-IUS were inserted by medical residents, generalists, or nurses, with no differences in expulsion rates or removal for personal reasons (Laporte et al, 2020). The expulsion rate (8.6%) was higher than the one found in the literature; however, it can be deemed acceptable once we are in training service, and more than 70% of women that desire for IUD have access to the method (Trussell, 2011).…”
Section: Discussionmentioning
confidence: 78%
“…& Donnon, 2016, p.). It is more frequent that IUD training is held at hospital institutions, linked to universities or family planning clinics(Dermish et al, 2016;Laporte et al, 2020;Thompson et al, 2016).Few studies reported training in IUD insertion for resident physicians in the primary care setting or in Latin America, including performance evaluation(Geary et al, 2017;Jatlaoui et al, 2017;Laporte et al, 2020;Stewart et al, 2016). In primary care cohort, trained FM physicians said that they felt confident about the training, but the obstacle reported for IUD offer and insertion was the payment, which was not cost-effective in the practice(Stewart et al, 2016).…”
mentioning
confidence: 99%
“…In Brazil, the prevalence is less than 2% in women of childbearing age. 1 Health services are having an organizational barrier that hinders Brazilian women to use this contraceptive method. Among these barriers, there is the limitation of the performance of other health professionals, other than the doctor, in the insertion of the IUD, since the multidisciplinary team is not always qualified or available to perform the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Despite the relevance of this practice, especially in women's health area, there is a gap in the knowledge about competences exercised by nurses in the insertion of the IUD. 1,10 Also, an instrument that directs the teaching of IUD insertion of these professionals was not identified in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…En effet, lorsque des infirmières avaient reçu une formation, les taux d'expulsion n'étaient pas plus élevés que si un médecin l'avait effectuée. Grâce à ces infirmières, cette méthode peut donc être accessible aux femmes dans les régions dépourvues de médecin spécialiste[25]. La formation des médecins gynécologues, leurs attitudes et leurs perceptions de la contraception sont des points importants à considérer.…”
unclassified